To find the vertex of the quadratic equation \(y = x^2 - 16x + 14\) by completing the square, follow these steps:
-
Start with the original equation: \[ y = x^2 - 16x + 14 \]
-
Group the \(x\)-terms and rewrite the equation: \[ y = (x^2 - 16x) + 14 \]
-
Complete the square for the expression \(x^2 - 16x\): \[ \text{Take half of } -16, \text{ which is } -8, \text{ and square it: } (-8)^2 = 64. \]
-
Add and subtract 64 inside the parentheses: \[ y = (x^2 - 16x + 64 - 64) + 14 \] \[ y = (x - 8)^2 - 64 + 14 \] \[ y = (x - 8)^2 - 50 \]
-
Now the equation is in vertex form \(y = a(x - h)^2 + k\), where \((h, k)\) is the vertex. Here, \(h = 8\) and \(k = -50\).
Therefore, the vertex of the quadratic equation \(y = x^2 - 16x + 14\) is: \[ \boxed{(8, -50)} \]